Polyvalence of the Cave Paradigm: Iris Murdoch’s Reception - Aliona Matiychak (Pitannâ Lìteraturoznavstva, 2018)
The article analyzes the literary and philosophical aspects of the Cave paradigm both in the context of Iris Murdoch’s fiction and her philosophical essays. The purpose of the article is to study the specifics of the Cave paradigm embodiment in the genrelogic structure of Murdoch’s philosophical novel. The multiple-aspect approach to the issue is proposed. In addition to the gnoseologic and gender aspects much attention is paid to the ethic-aesthetic structure component of Murdoch’s literary texts. Investigation of this paradigm in such view makes it possible to realize the resources of the author's style, emphasizing the connection between the author's ethics and the aesthetics of her fiction. In this case the proto-text is the famous Plato's myth about the Cave and the meta-text to reveal Murdoch's reception of this myth and interpretations in her novels are her own writings: “The Sovereignty of Good over other Concepts”, “The Fire and the Sun: Why Plato Banished the Artists”, “Concepts of Unity. Art”. As for cognition, likewise Plato, Murdoch regards the idea of Good has a limit, and it is vaguely recognizable, but having recognized it, we come to the conclusion that it is precisely the cause of all that is the true and beautiful. Developing the metaphor of the sun, as the understanding of the Good, Murdoch finds it extremely rich. Unlike her theoretical and philosophical writings, in her novels Murdoch ironically plays with the Plato's myth. She considers the Cave as a “magic space”, “theatre space”, “sacred space”, “place of initiation” or a “place of illusions”. The author's interpretation of the Cave paradigm is unique, worthy of a true philosopher. It is revealed by means of the material (topos) and spiritual (logos) factors correlation.Overall, this is no longer a real topos, but the consciousness of her characters as such, with all its mazes, shadows, dark corners, unconscious queer illusions.